FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN HIPERTENSI PADA LANSIA DI DESA SIGAOL SIMBOLON KABUPATEN SAMOSIR TAHUN 2013 - Martati Siringoringo; drh Hiswani, M.Kes; Drs Jemadi, M.Kes (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Hypertension is one of the degenerative disease a public health problem in the world because hypertension often appears without symptoms. Health Research Association (Riskesdas) Balitbangkes in 2007 showed the prevalence of hypertension nationally reached 31,7%. According to the Ministry of Health of the Republic of Indonesia (2010) suggested that hypertension is the third cause of death is by PMR 6,7% of the population deaths in all age groups in Indonesia. To determine factors associated with hypertension in Desa Sigaol Simbolon Kabupaten Samosir in 2013, conducted research using cross sectional design. The sample was 179 people  were taken by non random with purposive sampling. Univariate data were analyzed descriptively and bivariate data were analyzed using the chi square test with 95 % CI. Based on the results obtained proportion prevalance of hypertension 62,01 %, the highest proportion of respondents with hypertension in this age group is the age group 60-74 years (74,57%), female (63,16%), elementary education/equivalent (66,67%), employment status work (68,75%), family history (84,00%), nutritiona status obesity (72,73%), and insufficient physical activity (70,97%), have the habit of smoking (63,64%), saturated fat >3 times/week (71,05%), eating salt ≤ 3 times/week (67,65%). Results of the bivariate analizes, in general there is a significant association between age (p=0,041), family history (p=0,000,), and the habit of eating saturated fat (p=0,032) and the incidence of hypertension. And there was no significant relationship between gender, level of education, employment, nutritional status, physical activity, smoking habit, and the habit of eating natrium with incident hypetension. In Posyandu elderly should be done counseling about the risk factors and the prevention of hypertension. Elderly should set the pattern of consumption of saturated fats and checking the blood pressure every week regularly. Keywords: Hypertension, Elderly, Risk Factors